(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
High blood sugar levels are a hallmark of a verity of metabolic disease together referred to as Diabetes mellitus (DM). It is divided into two categories: (type 1 DM) and (type 2 DM). Type 1 diabetes results from a complete or nearly complete lack of insulin, while type 2 diabetes includes various disorders marked by differing levels of insulin resistance, impaired insulin secretion, and increased glucose production. This report presents a case of a newly diagnosed type 2 diabetes patient who received three follow-ups with Katankateriyadi Kwatha over three months (90 days). Following treatment, there were reductions in the patient’s fasting blood glucose, post-prandial blood glucose levels and HbA1c levels. Further-more, no adverse effects were observed. The finding in this clinical study are encouraging and provide evidence supporting the effectiveness of Katankateriyad Kwatha in reducing type 2 diabetes mellitus in a patient.